2021
DOI: 10.1111/jocd.14111
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intra‐arterial thrombolytic therapy for vision loss resulting from hyaluronic acid filler embolization

Abstract: Hyaluronic acid (HA) cosmetic injection is a minimally invasive and nonsurgical, rejuvenating therapy used in China and overseas. It is effective and nonsurgical and significantly reduces downtime. HA could be used as a soft tissue filler given its glycosaminoglycan structure, which promotes water retention and consequently volumizes and outlines the skin contour. 1 With the rapidly growing application of HA injections, the numbers of reported cosmetic injection complications have also incrementally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…A large number of aesthetic practitioners without strict professional training, lack the necessary knowledge of ophthalmic side effects and complications, and miss the optimal treatment timing. 5,[7][8][9][10] During glabellar injection, the needle may puncture small arteries and then fillers invade the ophthalmic artery and its branch with high injection pressure. 11 The central retinal artery is the first branch that nourishes the inner retinal layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of aesthetic practitioners without strict professional training, lack the necessary knowledge of ophthalmic side effects and complications, and miss the optimal treatment timing. 5,[7][8][9][10] During glabellar injection, the needle may puncture small arteries and then fillers invade the ophthalmic artery and its branch with high injection pressure. 11 The central retinal artery is the first branch that nourishes the inner retinal layers.…”
Section: Discussionmentioning
confidence: 99%
“…After an emergency IATT with 1500U hyaluronidase and 30mg papaverine superselected to the opening of the left ophthalmic artery, digital subtraction angiography revealed that the blood flow of the embolized ophthalmic artery was significantly accelerated (Figure 4A and B). 5 Assisted by traditional sequential therapy (high-dose pulsed methylprednisolone, alprostadil, neurotrophic agents, mannitol and other general symptomatic treatments), the patient reported a slight recovery of eyelid movement and reacquired light perception on the first postoperative day. Fundus photography revealed segmental changes in the branch retinal arteries.…”
Section: Case Reportmentioning
confidence: 98%
“…The clinical presentation of FIVO varies with the vascular configuration of the affected tissues. For instance, filler-induced injuries stemming from type III dissemination in the supratrochlear artery (STrA)—in which the artery distal to the injury site is occluded—show a multitude of ischemic skin patterns ( Figure 14 ) [ 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 ]. These variations reflect the presence of existing anastomoses between the STrA and the dorsal nasal artery, paracentral artery, supraorbital artery, and distal branches of the anterior division of the superficial temporal artery [ 194 ].…”
Section: Pathophysiology Of Ha-mediated Vascular Occlusionmentioning
confidence: 99%
“…( a ) Early ischemic changes (livedo reticularis) hours after dorsal nasal injection, showing involvement of the right supratrochlear territory, paracentral vessels, and dorsal nasal arterial regions; used with permission from Lucaciu et al [ 187 ]. ( b ) Early ischemic changes 6 h following glabellar HA filler injection, demonstrating involvement of the left supratrochlear artery, paracentral vessels, dorsal nasal territories, and infraorbital region; used with permission from Xu et al [ 188 ]. ( c ) Ischemic skin changes 24 h following accidental vascular occlusion resulting from nasal dorsal augmentation with HA filler, showing involvement of the left supratrochlear, left supraorbital, and bilateral dorsal nasal arteries; used with permission from Eldweik [ 193 ].…”
Section: Figurementioning
confidence: 99%
“…The increasing use of HA as a cosmetic filler in facial injection surgery and/or irregular procedures can result in complications such as bleeding, infection, and vascular embolism. Vascular embolism is often the most serious and urgent complication 1,2 . Lingual artery occlusion resulting due to filling of HA in the chin has been previously reported 3 .…”
Section: Introductionmentioning
confidence: 98%